HIV diagnoses in indigenous peoples: comparison of Australia, Canada and New Zealand - Shea, Beverley; Aspin, Clive; Ward, James; Archibald, Chris; Dickson, Nigel; McDonald, Ann; Penehira, Mera; Halverson, Jessica; Masching, Renee; McAllister, Sue; Smith, Linda Tuhiwai; Kaldor, John M.; et al. (International Health, 2011)
In industrial countries, a number of factors put indigenous peoples at increased risk of HIV infection. National surveillance data between 1999 and 2008 provided diagnoses for Aboriginal and Torres Strait Islanders (Australia), First Nations, Inuit and Métis (Canada excluding Ontario and Quebec) and Māori (New Zealand). Each country provided similar data for a non-indigenous comparison population. Direct standardisation used the 2001 Canadian Aboriginal male population for comparison of five-year diagnosis rates in 1999–2003 and 2004–2008. Using the general population as denominators, we report diagnosis ratios for presumed heterosexual transmission, men who have sex with men (MSM) and intravenous drug users (IDU). Age standardised HIV diagnosis rates in indigenous peoples in Canada in 2004–2008 (178.1 and 178.4/100 000 for men and women respectively) were higher than in Australia (48.5 and 12.9/100 000) and New Zealand (41.9 and 4.3/100 000). Higher HIV diagnosis rates related to heterosexual contact among Aboriginal peoples, especially women, in Canada confirm a widening epidemic beyond the conventional risk groups. This potential of a generalised epidemic requires urgent attention in Aboriginal communities; available evidence can inform policy and action by all stakeholders. Although less striking in Australia and New Zealand, these findings may be relevant to indigenous peoples in other countries.